Theoretical Study of Green Human Resources Management and the Effect of Job Satisfaction on Employee Performance - Prasetyo, Ahmad Fajar; Rahman, Aditya Nur; Bagasghani, Iqbal S.; Djastuti, Indi; Yuniawan, Ahyar (Research Horizon, 2024)
This theoretical study is a study to examine Green Human Resources Management practices among company employees. Despite much research on GHRM, there is no holistic model that addresses its impact on organizational, individual, and team performance. This research aims to examine 190 GHRM papers and build a holistic model in the application of the GHRM concept mediated by Job Satisfaction and its relationship to Employee Performance. Design/Methodology/approach through a literature review, this research analyzes related research results from various scientific disciplines relevant to the topic. The findings of this research found that the role of GHRM and job satisfaction are key success factors in creating good employee performance. Organizations need to implement GHRM, because this has an impact on employee satisfaction and increases employee job satisfaction to increase GHRM so that it can influence employee performance holistically. The limitation of this research is that it is only a literature review, it does not consider questionnaire surveys and workplace evaluations as future research opportunities. The originality/value of this research integrates theoretical studies regarding GHRM and job satisfaction which results in the importance of the company's role in human resource management practices in improving performance.